The Implementation of Mobile Health (mHealth) for Early Detection and Management of Catastrophic Disease Emergencies - JUNITA BR.TARIGAN (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Non-communicable diseases are a type of disease that can have a very big impact both socially and economically, for the sufferer, for the family and also for the government because treating it takes a very long time. Some diseases included in this catastrophic category are hypertension, diabetes mellitus (DM), and stroke. The aim of this research activity is to increase understanding and early prevention efforts against catastrophic diseases in all age groups. This research was carried out through several stages, including outreach, examination of early detection of risk factors for catastrophic diseases, counseling and training on measuring blood pressure and height and also on the use of online consultation applications. The results of this research show that public knowledge about catastrophic diseases has increased significantly. This socialization is very important to increase public awareness about catastrophic diseases, with the aim of enabling people to carry out early detection, rapid treatment, and control risk factors to reduce the level of disease and death due to these catastrophic diseases.